The Death of Cash? Not So Fast: Demand for U.S. Currency at Home and Abroad, 1990-2016 - Ruth Judson (Deutsche Bundesbank, 2017)
It would seem that physical currency should be fading out as the world of payments is increasingly electronic, with new technologies emerging at a rapid pace, and as governments look to restrictions on large-denomination notes as a way to reduce crime and tax evasion. Nonetheless, demand for U.S. dollar banknotes continues to grow, and consistently increases at times of crisis both within and outside the United States because it remains a desirable store of value and medium of exchange in times and places where local currency or bank deposits are inferior. After allowing for the effect of crises, demand for U.S. banknotes appears to be driven by the same factors as demand for other types of money, with no discernible downward trend. In this work, I review developments in demand for U.S. currency since the collapse of Lehman Brothers in late 2008 with a focus on some new questions. First, what are the factors driving demand for lower denominations, especially 20s, which are the most commonly used in domestic transactions? To what extent can the recent strength in demand be attributed to the long spell of very low interest rates? Finally, for the larger denominations, I revisit the question of international demand: I present the raw data available for measuring international banknote flows and presents updates on indirect methods of estimating the stock of currency held abroad. These methods continue to indicate that a large share of U.S. currency is held abroad, especially in the 100 denomination. As shown in an earlier paper, once a country or region begins using dollars, subsequent crises result in additional inflows: the dominant sources of international demand over the past two decades are the countries and regions that were known to be heavy dollar users in the early to mid-1990s. While international demand for U.S. currency eased during the early 2000s as financial conditions improved, the abrupt return to strong international demand that began nearly a decade ago with the collapse of Lehman Brothers in 2008 has shown only limited signs of slowing. In contrast, the growth rate of demand for smaller denominations is slowing, perhaps indicating the first signs of declining domestic cash demand.
Keywords: C82; E4; E49; 330; currency; banknotes; dollarization; crisis